If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4p + 2 + 2p + 1 = 8 Reorder the terms: 2 + 1 + 4p + 2p = 8 Combine like terms: 2 + 1 = 3 3 + 4p + 2p = 8 Combine like terms: 4p + 2p = 6p 3 + 6p = 8 Solving 3 + 6p = 8 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 6p = 8 + -3 Combine like terms: 3 + -3 = 0 0 + 6p = 8 + -3 6p = 8 + -3 Combine like terms: 8 + -3 = 5 6p = 5 Divide each side by '6'. p = 0.8333333333 Simplifying p = 0.8333333333
| -5x+9=17-x | | 6y=8x-10 | | 10t^2=12t+23 | | C+c=73 | | -3(-4-6y)+7(y+5)= | | 75+2x=0-15 | | 4+x=200 | | 4x^2+4x+32=0 | | 4x+1+3x=-3 | | 2x^2+3+3=-7x | | Y=2x+(-8) | | -15x+9=17-x | | 4X-8=3(2X-4) | | 75+2x=15 | | X+2=2overy-1 | | +t/12=-3 | | -6b+28=9b-2 | | 3x-9=4x-24 | | 3(4x+1)=3+12x-3 | | 36+2y-15=12y-9-5y | | 8-4+2R-4R+8R= | | 2L+2W=W+84 | | 8-r=3r-14 | | x-1b=72 | | .666h-9=6-.666h | | 8x+6y-10=0 | | 24b+4=52 | | (x-3)(x-4)-(x+4)=0 | | 2n^3-24n^2-23048n=0 | | 4.3+7.5=5.8 | | 10v^2=11v+6 | | -3-10=-46 |